Improving Fiqih Learning Results Through the Make a Match Method at MTS Darus Salam Probolinggo - Devy Habibi Muhammad; Mutiah Cahyaning Tiyas (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to explore learning innovations in Fiqh subjects in class VII MTs Darus Salam Probolinggo using the Classroom Action Research (PTK) method. Currently, education is experiencing many changes in various aspects of people's lives. This is caused by the globalization process, which affects the whole world, including Indonesia, and the rapid progress of technology and science. The latest educational paradigm requires teachers to make learning more student-centered, however the results of formative tests and daily tests show that students' ability to understand and explain the thaharah chapter is still lacking. Therefore, researchers try to use the make a match method as a solution to improve student learning outcomes. The research results showed that after implementing the make a match method, there was a significant increase in the level of student learning completion. Thus, the use of the make a match method can be a new alternative that is useful for Fiqh subject teachers in improving student learning outcomes, and can also be applied to other subjects.